Retrospective analysis of laparoscopic salpingostomy and conservative expectant management of tubal ectopic pregnancy - Takashima, Kunitomo (Reprod Med Biol, 2009)
PURPOSE: To identify predictive factors for successful expectant management of ectopic pregnancy and to evaluate the prognosis for fertility after expectant management and laparoscopic salpingostomy. METHODS: Forty‐six cases of expectant management and eighty cases of laparoscopic salpingostomy for tubal ectopic pregnancy were retrospectively analyzed. Subjects were classified in three groups: those who underwent laparoscopic salpingostomy, those treated by expectant management only, and those treated by expectant management but requiring additional treatment. RESULTS: The rates of tubal patency, intrauterine pregnancy and repeated ectopic pregnancy in the laparoscopic salpingostomy group were 75, 40, and 16%. The rates in the expectant management group were not significantly different: 72, 42 and 15%. Finally, the rates in the extra treatment group were 75, 39 and 15%. Success rate of expectant management was 54%. In 93% of cases expectant management was successfully completed when the initial levels of urinal hCG were less than 3000 mIU/ml and the levels of hCG 48 h later were less than 80% of the initial levels. However, expectant management alone was insufficient and required extra treatment in 90% of cases when the initial levels of hCG were 3000 mIU/ml and above or when the levels of hCG level 48 h later was 80% of initial levels and above. CONCLUSIONS: Expectant management in combination with salpingostomy is not only minimally invasive but also a useful way to preserve fertility. Initial urine hCG levels and their variation over time can help predict whether expectant management will succeed.